Continuous Integration and Automation for Devops - Schäfer, Andreas; Reichenbach, Marc; Fey, Dietmar (IAENG Transactions on Engineering Technologies Special Edition of the World Congress on Engineering and Computer Science 2011, 2013)
The task of managing large installations of computer systems presents a number of unique challenges related to heterogeneity, consistency, information flow and documentation. The emerging field of DevOps borrows practices from software engineering to tackle complexity. In this paper we provide an insight in how automation can to improve scalability and testability while simultaneously reducing the operators' work. © 2013 Springer Science+Business Media.
UnivIS-Import:2015-04-20:Pub.2013.tech.IMMD.IMMD3.contin
Keywords: Administration; Automation; DevOps; eLearning; Heterogeneous Systems; System Management